Pengaruh Manajemen Rantai Pasok, Pemanfaatan Inovasi Teknologi Dan Kolaborasi Rantai Pasok Terhadap Kinerja Operasional Rumah Kopi - Tuankota, Aulia Laksmi; Latuconsina, Zainuddin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to empirically test the influence of supply chain management, the use of technological innovation, and supply chain collaboration on the operational performance of coffee houses. This type of research is quantitative research. The population used in this study is the population of all Coffee Houses in Ambon City. The sample used in this study is 30 coffee house owners who have implemented the use of technological innovation. Sampling in this study uses porposive sampling technique. By using a question instrument (questionnaire) to obtain primary data from the owners of Coffee Houses in Ambon City. The data obtained was then analyzed using partial least square (PLS) in testing structural equation modeling (SEM) with the help of XLSTAT PLS-PM 2014 software. The results of the study prove that: 1) Supply chain management has a positive relationship with the operational performance of coffee houses in the city of Ambon. 2) Technological innovation does not have a positive relationship with the operational performance of coffee houses in the city of Ambon. 3) Supply chain collaboration has a positive relationship with the operational performance of coffee houses in the city of Ambon.